Caracterização morfométrica e temporal do crescimento de Urochloa brizantha cv. Marandu para calibração do modelo CROPGRO forragem - Cunha, Daniel da (2018)
Growth analysis is one of the several methods used to describe the morphophysiological changes on plants throughout their life cycle. Such changes are caused by genetic, environmental and management variations. The objective of this work was to characterize, describe and modeling the growth and development of Urochloa brizantha cv. Marandu and parameterize the CROPGRO Forage Model by changes in coefficients related to the initial growth. An experiment was conducted to collect plant growth data, where the plants were grown in pots with 6 dm-3 capacity of corrected and fertilized substrate as recommended for sowing. Fertilization and maintenance irrigation were performed throughout the experiment for the homogeneity of growth conditions. Seeds were used per pot buried at 25 mm depth. After thinning two plants were maintained per pot. The experimental design was completely randomized, using 90 pots and three replicates per evaluation in 30 times after sowing. In addition to seedling emergence, monitoring, all phenological stages were identified throughout the plant life cycle, including vegetative, reproductive and floral development. During growth, the tissue flow was monitored, weekly destructive pots evaluations were performed with separations of the plant morphological components in leaves, stem, dead leaves, crowns and roots. The leaf area was determined, and the morphological components were dried separately in a forced-draft oven at 55 °C for 72 hours and then weighed. The response patterns of the variables were represented at different time scales of development. The experimental data related to the dry mass production and information related to the initial conditions of planting, crop management and those related to the meteorological data during the experimental period were organized as the input files in the DSSAT Platform. The latest version of the CROPGRO Forage Model calibrated for Marandu grass in 2017 was used as the starting point for the simulations related to the initial growth and development of the plants. The characterization of the phenological and growth stages obtained by the morphogenic and morphophysiological evaluation provided subsidies for the calibration of the model. There was a significant improvement in the simulation of forage growth and in the determination of the phenological phases of the model. More accurate growth curves have also been established in simple production models based on weather conditions. The present study provides a subsidy for the exploration of forage grasses in a conscious way and allows more precise simulations of growth and development to be carried out reducing the risks in the management decision-making.